KECEMASAN AKADEMIK DENGAN PRESTASI BELAJAR PADA MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA - Wahyu Aulizalsini Alurmei; Farhan Saputra, Audria Sharon Prameswari, Mochamad Refa Mulya Dewa, Mochamad Gani Gynastiar (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
By looking at current educational developments, we realize that the psychological component is very important for academic success. It cannot be denied that a student's behavior can affect his or her achievement at school. Anxiety in the lecture environment is one of the problems that arise during the educational process. When faced with situations that challenge their thinking, many students experience anxiety. The aim of this research is to identify whether there is a relationship between academic anxiety and psychology students at Bhayangkara University. This research uses a quantitative descriptive approach. The research subjects were students of the Bhayangkara University Psychology Program. The quota sampling method is taking samples from a population that has certain characteristics to obtain the desired sample size. The researcher's questionnaire was administered via Google Form to collect data. Data analysis was carried out by applying correlation test techniques, in accordance with the research hypothesis, to identify the relationship between anxiety levels and learning achievement. This study found that the anxiety level of students in the Bhayangkara University Psychology Study Program delayed their learning outcomes. The validity test results showed 14 valid items, and the reliability test showed a score of 0.735 for reliable information. Students also tend to distract themselves with other activities rather than focusing on studying. Apart from that, their lack of self-confidence seems to be reflected in their imagination on certain questions, which then has an impact on their learning achievement.